Facile synthesis and anticancer activity of C-10 non-acetal deoxoartemisinin dimers - Supannee Phothongkam (2018)
In this research, N-(2-aminoethyl)glycine-linked C-10 non-acetal deoxoartemisinin dimers were synthesized by using solution phase peptide synthesis approach. In addition, chemical modification of the C-10 non-acetal deoxoartemisinin monomers and dimers by adding a lysine unit to the N-terminus has been performed. The biological activities of all synthesized compounds were evaluated against the colon cancer cell line (Caco-2). The non-acetal deoxoartemisinin monomers 12a, 15a-c and dime rs 13a, 16a-c were active against Caco-2 cells and more potent than dihydroartemisinin. © 2012 Elsevier Ltd. All rights reserved.